Evaluation of a psycho-oncological intervention model in the peridiagnosis for adult patients - Demateis, Mariano; Castañeiras, Claudia; Llull, Dario (Psicooncología, 2024)
Objetive: Cancer diagnosis impacts diverse aspects of a patient’s life. Their adjustment should be assessed according to the phase of the oncologic course, being emotional activation (AE) and illness representation (RE) its two medullary components. A psychosocial intervention was developed for the peridiagnosis phase, characterized by specific features and demands. This paper aims to present findings resulting from the application of the Model of Psychooncological Intervention in Peridiagnosis (MIPP) in adult patients. Method: A randomized experimental study was conducted with 50 newly diagnosed patients (in the week following the first consultation with the oncologist), attended by the oncology service of the Santamarina Hospital (Tandil, Argentina). AE was assessed with DASS 21, RE with BIPQ-R and adjustment to cancer with miniMAC, on the first (pre) and last (post) day of protocol application. Results: Significant positive differences and large effect sizes were obtained in the between-group comparison (intervention/control) in the pre/post measures for the variables AE and RE. In within-group (intervention) analysis, statistical significance was maintained, with medium and large effect sizes. Conclusions: The implementation of the MIPP had a significant impact of clinical relevance on adjustment to cancer in the first phase of the oncologic course in adult patients.
Keywords: psycho-oncology; peridiagnostic; emotional activation; illness representation; psychological intervention; adjustment to cancer